Special issue dedicated to ICFP 2014: Editorial. (25th October 2016) - DREYER, DEREK; SHEERAN, MARY
Abstract : The 19th ACM SIGPLAN International Conference on Functional Programming (ICFP) took place on September 1–3, 2014 in Gothenburg, Sweden. After the conference, the programme committee, chaired by Manuel Chakravarty, selected several outstanding papers and invited their authors to submit to this special issue of JFP. We acted as editors for these submissions. This issue includes the six accepted papers, each of which provides substantial new material beyond the original conference version. The selected papers demonstrate both the quality and the breadth of the conference, with a strong emphasis on types and their applications, and ranging from compilation methods through contract verification to homotopy type theory.